Regional Development Inequality and Political Representation: Southern West Java's Marginalization in Provincial Policy-Making - Arif naufal a's adi (Journal of Political Innovation and Analysis, 2025)
This study explores the regional development inequality and political representation in West Java, Indonesia, with a particular focus on the southern regions' marginalization in provincial policymaking. The objective is to investigate how unequal political representation in the provincial legislature affects the allocation of resources, infrastructure development, and overall regional inequality. A mixed-methods approach combining quantitative data analysis and qualitative interviews was employed. The quantitative phase involved analyzing secondary data from 27 districts in West Java over the period 2015–2024, covering development indicators such as the Human Development Index (HDI), infrastructure quality, and budget allocation. The qualitative phase focused on in-depth interviews with local officials, legislators, and community leaders to understand the mechanisms of political marginalization. The findings reveal a significant disparity in political representation between southern and northern West Java, with the southern regions holding fewer legislative seats and experiencing lower levels of infrastructure investment and public service allocation. The research suggests that political representation is a key determinant of regional development outcomes, with underrepresented regions facing slower development and exacerbated inequality. The study calls for electoral reforms, equitable budget allocation mechanisms, and the creation of independent regional monitoring bodies to address these disparities and promote more inclusive development